A visual bi-layer indicator based on roselle anthocyanins with high hydrophobic property for monitoring griskin freshness. (1st September 2021) - Zhang, Junjun; Huang, Xiaowei; Shi, Jiyong; Liu, Li; Zhang, Xinai; Zou, Xiaobo; Xiao, Jianbo; Zhai, Xiaodong; Zhang, Di; Li, Yanxiao; Shen, Tingting
Graphical abstract: Highlights: The PVDF film was first used as a moisture prevent-layer of freshness indicator. The PSRF film showed highest hydrophobic property and color stability. The PSRF film has been successfully used as a visual indicator for monitoring griskin freshness. Abstract: This study designed a new type indicator with hydrophobic Polyvinylidene Fluoride (PVDF) film as a moisture prevent-layer. And the sensor layer was provided based on polyvinyl alcohol/Sodium alginate (PS) and Roselle anthocyanins (RAs). Physical properties, microstructure, and color stability of the bi-layer indicator have been investigated. The Water contact angle (WCA) of PS/RAs/ PVDF film (PSRF) was 108.85°, which can be considered as an excellent hydrophobic surface. The lowest Water Vapor Permeability (WVP) value of PSRF exhibited a good barrier property for moisture. Therefore, PSRF film was used to monitor the griskin freshness. The Total volatile basic nitrogen (TVB-N) level was increased to 18.02 mg/100 g at 72 h, and the color of the indicator presented visible color changes. The acquired results revealed a good correlation between TVB-N, pH and color change of the indicator. The research indicated that PSRF indicator has increasing potential application on food intelligent packaging.